STRUCTURAL-STRATEGIC APPROACHES TO COUPLE AND FAMILY THERAPY STRUGULING WITH ABUSE AND DOMESTIC VIOLENCE - USM ADMIN (Moldova State University, 2018)
The issue and the key concepts and strategies that can be successfully used when providing couple therapy as part of the systemic therapy interventions using the basic concepts of strategic and structural family therapy are treated in the article. The two models, structural family therapy (as developed by Salvador Minuchin) and strategic family therapy (as developed by Jay Haley), are presented together because of their common emphasis on systems and structure. Both approaches aim to realign family organization to produce change in the entire system, and both are focused on the hierarchical organization of the family. The key perspective of this article is to present the Cloe Madanes approach and preconditions, and possible directions of interventions with families that experience domestic violence. Keywords: structural family therapy, strategic therapy, family violence, couple therapy, psychotherapy, coalitions, maladaptive transactions, accommodation, systemic psychotherapy, interpretation, boundaries, differentiation.